Does Combination Therapy with Statins and Fibrates Prevent Cardiovascular Disease in Diabetic Patients with Atherogenic Mixed Dyslipidemia? - Agouridis, Aris P. (SBDR - Society for Biomedical Diabetes Research, 2013)
Type 2 diabetes mellitus (T2DM) is associated with the development and progression of cardiovascular disease (CVD). Statins have an established efficacy in the management of dyslipidemia primarily by decreasing the levels of low-density lipoprotein cholesterol and thus decreasing CVD risk. They also have a favorable safety profile. Despite the statin-mediated benefit of CVD risk reduction a residual CVD risk remains, especially in T2DM patients with high triglyceride (TG) and low high-density lipoprotein cholesterol (HDL-C) values. Fibrates decrease TG levels, increase HDL-C concentrations, and improve many other atherosclerosis-related variables. Fibrate/statin co-administration improves the overall lipoprotein profile in patients with mixed dyslipidemia and may reduce the residual CVD risk during statin therapy. However, limited data exists regarding the effects of statin/fibrate combination on CVD outcomes in patients with T2DM. In the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study the statin/fibrate combination did not significantly reduce the rate of CVD events compared with simvastatin/placebo in patients with T2DM. However, it did show a possible benefit in a pre-specified analysis in the subgroup of patients with high TG and low HDL-C levels. Furthermore, in the ACCORD study the simvastatin/fenofibrate combination significantly reduced the rate of progression of retinopathy compared with statin/placebo administration in patients with T2DM. The present review presents the available data regarding the effects of statin/fibrate combination in patients with T2DM and atherogenic mixed dyslipidemia.